Sequencing, Expression, and Functional Analyses of Four Genes Related to Fatty Acid Biosynthesis During the Diapause Process in the Female Ladybird, Coccinella septempunctata L. - Xiang, Mei; Zhang, Hong-Zhi; Jing, Xiao-Yu; Wang, Meng-Qing; Mao, Jian-Jun; Li, Yu-Yan; Zang, Lian-Sheng; Zhang, Li-Sheng (Frontiers in Physiology, 2021)
The ladybird Coccinella septempunctata L., a predatory insect, serves as an excellent biological control agent against common agricultural pests. It undergoes a diapause phenomenon, during which a large amount of fat accumulates in the abdomen. A comprehensive analysis of this lipid accumulation can reveal the molecular mechanisms underlying diapause regulation, which can be exploited to improve the shipping and transport of the insect for agricultural applications. In this study, we compared the transcriptome of C. septempunctata during non-diapause, diapause, and post-diapause and screened four key genes related to lipid metabolism. The cDNA of these four relevant enzymes, acetyl-CoA carboxylase (ACC), long-chain fatty acid-CoA ligase (ACSL), elongase of very-long-chain fatty acids (ELO), and very-long-chain 3-oxoacyl-CoA reductase (KAR), were cloned using reverse transcription-polymerase chain reaction and rapid amplification of cDNA ends. Their expression profiles were analyzed during the preparation and maintenance phases of diapause and the post-diapause phase. The functions of these four key enzymes in diapause were further verified using RNA interference. All four genes were most closely related to the homeotic gene from Tribolium castaneum. The expression profiles of these four genes were significantly affected under diapause-inducing conditions; their expression level was the highest in the diapause preparation phase, and it gradually decreased with the diapause induction time. RNA interference showed that the target genes play important roles in fat storage during early diapause, and the decrease in their expression leads to a decrease in lipid content in C. septempunctata. These results indicate an important role of ACC, ACSL, ELO, and KAR in lipid accumulation. Our findings could help elucidate the production and accumulation of lipids by insects during the preparation for diapause and improve biological control.